Intraoperative application of regional cerebral oxygen saturation monitoring for geriatric patients in China: a survey - Zhang, Jie; Shen, Haiyan; Wang, Huiping; Xiao, Feng; Deng, Lu; Chen, Xiang; Xie, Yongqiu (Frontiers in Medicine, 2023)
Background: Regional cerebral oxygen saturation (rSO2) monitoring is a real-time and noninvasive technique for estimating the balance of regional cerebral oxygen supply and consumption. Despite the growing popularity of this monitoring technique, data regarding outcome benefits remain sparse and contradictory. This study was conducted to explore the popularity and understanding of cerebral oxygen saturation monitoring during anesthesia in geriatric patients.Methods: An online self-report questionnaire was distributed in March 2021 to various hospital in China for dissemination to anesthesiologists. Questions surveyed cerebral oximetry equipment and utilization, demographics, and clinical practice of participants.In total, 447 anesthesiologists were responded. Of these, 301 (67.3%) responses reported that their hospitals were equipped with cerebral oximetry, which 274 anesthesiologists use it during anesthesia. A high percentage of anesthesiologists chose to monitor rSO2 during cardiac surgery (77.4%, n = 212) and neurosurgery (40.5%, n = 111). Most anesthesiologists agreed that a 30% reduction from rSO2 baseline requires intervention to avoid cerebral ischemia, mainly via elevating arterial pressure and FiO2. Of these without cerebral oximetry, 138 of 146 (94.5%) anesthesiologists are willing to monitor rSO2. In addition, 291 responses believed that cerebral oxygen monitoring would helpful for preventing postoperative cognitive dysfunction.Conclusion: Our survey indicated that the prevalence of cerebral oximetry remains relatively low, while almost all anesthesiologists expressed their willingness to use rSO2 monitoring in geriatric anesthesia. Heterogeneity in clinical practice was identified, indicating relevant knowledge gaps that should encourage further clinical research to optimize treatment.